Functional Analysis of a Carboxylesterase Gene Associated With Isoprocarb and Cyhalothrin Resistance in Rhopalosiphum padi (L.) - Wang, Kang; Huang, Yanna; Li, Xinyu; Chen, Maohua (Frontiers in Physiology, 2018)
Carboxylesterase (CarE) is an important class of detoxification enzymes involved in insecticide resistance. However, the molecular mechanism of CarE-mediated insecticide resistance in Rhopalosiphum padi, a problematic agricultural pest, remains largely unknown. In the present study, an isoprocarb-resistant (IS-R) strain and a cyhalothrin-resistant (CY-R) strain were successively selected from a susceptible (SS) strain of R. padi. The enzyme activity indicated that enhanced carboxylesterase activity contributes to isoprocarb and cyhalothrin resistance. The expression levels of putative CarE genes were examined and compared among IS-R, CY-R and SS strains, and only the R. padi carboxylesterase gene (RpCarE) was significantly overexpressed in both the IS-R and CY-R strains compared to the SS strain. The coding region of the RpCarE gene was cloned and expressed in Escherichia coli. The purified RpCarE protein was able to catalyse the model substrate, α-naphtyl acetate (Kcat = 5.50 s-1; Km = 42.98 µM). HPLC assay showed that the recombinant protein had hydrolase activity against isoprocarb and cyhalothrin. The modelling and docking analyses consistently indicated these two insecticide molecules fit snugly into the catalytic pocket of RpCarE. Taken together, these findings suggest that RpCarE plays an important role in metabolic resistance to carbamates and pyrethroids in R. padi.